Diversity of Staphylococcus species and prevalence of enterotoxin genes isolated from milk of healthy cows and cows with subclinical mastitis - Rall, V. L. M. [UNESP]; Miranda, E. S. [UNESP]; Castilho, I. G. [UNESP]; Camargo, C. H. [UNESP]; Langoni, Hélio [UNESP]; Guimaraes, F. F. [UNESP]; Araujo Junior, J. P. [UNESP]; Fernandes Junior, A. [UNESP] (Elsevier B.V., 2014)
The objectives of this study were to determine the occurrence and diversity of Staphylococcus spp. in milk from healthy cows and cows with subclinical mastitis in Brazil and to examine the profile of enterotoxin genes and some enterotoxins produced by Staphylococcus spp. A total of 280 individual mammary quarter milk samples from 70 healthy cows and 292 samples from 73 cows with subclinical mastitis were collected from 11 farms in the state of Sao Paulo, Brazil. Staphylococcus spp. were recovered from 63 (22.5%) samples from healthy cows and from 80 samples (27.4%) from cows with mastitis. The presence of Staphylococcus aureus was significantly different between these 2 groups and was more prevalent in the cows with mastitis. The presence of Staphylococcus saprophyticus was also significantly different between these 2 groups, but this organism was more prevalent in healthy cows. No statistically significant differences were observed in the numbers of other staphylococci in milk samples from the 2 groups. The sea gene was the most prevalent enterotoxin gene in both groups. Eight of 15 (53.3%) Staph. aureus carried this gene and all produced the SEA toxin. In the coagulase-negative staphylococci (CNS) group, 61 of 128 (47.5%) had the same gene and just 1 (1.6%) Staphylococcus epidermidis strain produced the enterotoxin in vitro. Because CNS were isolated from both groups of cows and most CNS contained enterotoxin genes but did not produce toxins, the role of CNS in mastitis should be carefully defined.
Keywords: Staphylococcus aureus; coagulase-negative staphylococci; mastitis; enterotoxin